Bayer in talks with BASF to acquire vegetable seeds business (Western Farm Press, 2018)
The seed businesses being divested include the global cotton seed business (excluding India and South Africa), the oilseed rape/canola business in North America and Europe, and the soybean seed business. Any sales and licenses would be subject to a successful closing of the proposed acquisition of Monsanto, which remains subject to customary closing conditions, including receipt of required regulatory approvals.